From connected pathway flow to ganglion dynamics. Issue 10 (23rd May 2015) - Rücker, M.; Berg, S.; Armstrong, R. T.; Georgiadis, A.; Ott, H.; Schwing, A.; Neiteler, R.; Brussee, N.; Makurat, A.; Leu, L.; Wolf, M.; Khan, F.; et al.
Abstract During imbibition, initially connected oil is displaced until it is trapped as immobile clusters. While initial and final states have been well described before, here we image the dynamic transient process in a sandstone rock using fast synchrotron‐based X‐ray computed microtomography. Wetting film swelling and subsequent snap off, at unusually high saturation, decreases nonwetting phase connectivity, which leads to nonwetting phase fragmentation into mobile ganglia, i.e., ganglion dynamics regime. We find that in addition to pressure‐driven connected pathway flow, mass transfer in the oil phase also occurs by a sequence of correlated breakup and coalescence processes. For example, meniscus oscillations caused by snap‐off events trigger coalescence of adjacent clusters. The ganglion dynamics occurs at the length scale of oil clusters and thus represents an intermediate flow regime between pore and Darcy scale that is so far dismissed in most upscaling attempts.